The Agricultural Situation, January 1933 - Black, John D. (The Review of Economics and Statistics, 1933)
T HIS is not an appropriate time for entering into refinements in describing the agricultural situation. The essential facts in it are of such striking character that the details can largely be ignored. What is needed instead is a reasonable interpretation of the outstanding facts. That such an interpretation is not easy to make is emphasized by two divergent interpretations. A Special Committee of the Association of Land-Grant Colleges and Universities, composed of three Deans or Directors and three farm economists, after reviewing the facts in the case concluded as follows: In I927, the agricultural situation was characterized by moderate improvement in prices and income from the postwar collapse of I920-2I, but an unfavorable position in comparison with other groups still persisted.... Evidencing the incomplete recovery, land values were still moving downward, and the net shifts in population were toward the cities, where better opportunities seemed to prevail.... Even though all other groups have experienced reduced income (since then), the farmers' share of the national income in 1930 and I93I has been lower than in any preceding year, and the farmers' rewards for labor, management, and capital, have been placed on a still lower plane in relation to the returns of other groups. The report then affirms that restoration of agricultural prosperity is vital to the welfare of the nation and urges that a comprehensive program of relief be undertaken, even including improving prices of farm products through special price raising measures.' On the other hand, Dr. Joseph S. Davis of the Food Research Institute, who has given much attention to agriculture in the past ten years, in a paper before the American Farm Economic Association in Cincinnati in December, questions whether general disparity between prices of farm products and other prices has been proved, or that special price raising measures to correct such alleged disparities are needed or desirable.2 Surely it will not be easy to evaluate a situation lending itself to such divergent interpretations; and I shall not expect to accomplish this to the satisfaction of the parties named. The elements in the situation to be considered are production, prices, income, population, land values, and mortgage debt.